Formulation of antibiotic ointmentfrom the jatropha latex curcas - Khafniza, Khanafiah (2012)
Jatropha curcas is widely used in traditional folk medicine. Every part of the plant has its own advantages in treating diseases. The latex of this plant has strong antimicrobial activity. Secondary metabolites (tannins, saponins and flavonoids) that are present in the latex make it such a good antibacterial agent. It can be used as an antiseptic against cuts and wounds because of the healing effect. Even though the latex has been used traditionally as a plant medicament, scientific investigation including toxicological studies was very limited. Due to this condition, an antibiotic ointment is formulated using the dried latex of Jatropha as the active ingredient. The amounts of the active ingredient used in this experiment are 0.5g, 1.0g and 1.5g. In order to determine whether the cream is well formulated, the stability studies and the antimicrobial study are done. In vitro method is chosen to perform the antimicrobial test. It shows that as the active ingredient is increasing, the zone of inhibition is also increased. The potential of antimicrobial activities in the Jatropha latex is proven. Thus, antibiotic ointment can be used to kill microorganisms and prevent infections. The ointment is also shown good physical stability at room temperature and normal atmospheric condition after one month. Since the Jatropha latex has medicinal properties, it is potentially to be commercialized in industry.